"Wandering towards God over borders”. St. Paisius Velichkovsky and his role in the restoration of Bizantine-Slavic spirituality between the 18th and 20th centuries - Kocój, Ewa; Pelin, Valentina (Balcanica Posnaniensia. Acta et studia, 2009)
Saint Paisius Velichkovsky (1722–1794), canonised by the Russian Orthodox Church in 1988, is one of the key figures of Byzantine-Slavic spirituality in the 18th and 19th centuries. His life and work were marked by the search for an authentic monastic experience. The aim of the article is to show Paisius' role in the renewal of Hesychast spirituality and in shaping a model of monastic life that had a lasting impact on Orthodoxy in Central and Eastern Europe and Russia. The analysis is based on historical sources, manuscripts and translations of patristic texts preserved in Romanian and Russian monasteries, as well as literary testimonies of Paisius' disciples and hagiographic tradition. A comparative analysis method was used, covering monastic documents (rules, inventories, book registers) as well as sources on the development of Hesychasm. The results of the research indicate that Paisius's activity contributed to the renewal of three key dimensions of Orthodox spirituality: „starczestwo” (elders or spiritual fathers leadership), the practice of the Jesus Prayer, and extensive translation and editorial work. The communities initiated by the saint, multinational and open, also became a model of cenobitic life and centres of spiritual revival. The legacy of Paisius Velichkovsky, now referred to as „Paisianism”, became a new source of inspiration for Orthodoxy after the fall of communism.